EXPERIMENTAL STUDY AND ANALYSIS OF SOLAR ENERGY SYSTEM WITH GRID - Bharti, Pradeep; Sharma, A.K. (International Journal of Engineering Technologies and Management Research, 2017)
In this paper , we are discuss about the solar power and grid connection , in this way we are use the various component such as PV Cells battery inverter, and grid power , after that all component are assembled . This system is optimized design of grid-connected PV system with storage, which is suitable for appliances. This system has requires less installment cost and supplies residential loads with the grid.